Experimental Study of Carbon Dioxide Boiling Crisis in Near-critical Natural Circulation - ZENG Chengtian1, ZHOU Yuan1, HUANG Yanping2, LUO Qiao1, TIAN Gengyuan1, HUANG Jiajian1 (Yuanzineng kexue jishu)
Carbon dioxide is utilized as a direct coolant in micro-modular gas-cooled fast reactor cycle systems. The supercritical carbon dioxide cycle systems are attracted widespread attention for their compact design and high operating efficiency. In the case of a LOCA (loss of coolant accident) in carbon dioxide micro-modular gas-cooled fast reactors, the core pressure drops rapidly to a near-critical region. Near-critical carbon dioxide exhibits unique boiling heat transfer behavior due to its high saturation vapor density, low latent heat, and extremely low surface tension. The study of near-critical carbon dioxide heat transfer characteristics under conditions of physical distortion is critical to the design and evaluation of micro-modular gas-cooled fast reactor cycle systems. Experimental studies conducted in a closed loop under natural circulation and close to critical conditions. The boiling heat transfer characteristics of near-critical carbon dioxide was investigated. A typical experiment shows that under near-critical conditions ranging from 6.8 MPa to 7.2 MPa, the entire test section initially exhibites stable subcooled boiling. With a minimal power increase (0.6 kW/m2), the wall temperature at the outlet rises sharply and propagates upstream toward the inlet. The entire axial wall temperature rising phenomenon lasts approximately 800 s. During this period, inlet and outlet pressures, pressure differentials, and inlet temperature remain nearly constant, with a small increase in mass flux accompanying the increase in power. Enthalpy analysis indicate that subcooled boiling predominates throughout the axial bulk fluid. The low gas quality of the axial bulk fluid suggests a preliminary assessment of the departure from nucleate boiling (DNB). Subsequent analysis comprehensively examines the evolution of axial heat transfer deterioration under conditions of distorted properties and DNB-type boiling crises. The study highlights significant influences of pressure and inlet subcooling on the critical heat flux, with minimal effects observe from the natural circulation mass flux. The study focuses on the effect of mass flux on critical heat flux. The critical heat flux shows a consistent increasing trend with increasing mass flux. This trend reaffirms the DNB-type boiling crisis, because higher mass flux weakens boundary layer bubble formation, thus elevating the threshold for boiling crisis. A theoretical hypothesis was developed to explain the phenomenon of wall temperature rising propagating upstream under a minimal power increase in near-critical carbon dioxide natural circulation loops. This theoretical hypothesis combines a typical experimental analysis with an analysis of the effect of boundary conditions on the critical heat flux. The hypothesis outlines five sequential stages: stable nucleate boiling preceding the boiling crisis, a slight power increase triggering a boiling crisis similar to DNB at the outlet, heat transfer from high-temperature solid regions to cooler solid regions, vapor film formation due to bubble dynamics near critical conditions induced by wall overheating, and successive temperature rising culminating in an overall axial wall temperature increase.